Prediction of Total Egg Production from Partial or Cumulative Egg Production in a Stock of White Leghorn Hens in Iraq - Al-Samarai, Firas Rashad; Al-Kassie, Ghalib Alwan; Al-Nedawi, Ahmed M.; Al-Soudi, Kaild Abdul-Aziz (International Journal of Poultry Science, 2008)
A study of White Leghorn hens at a poultry farm, Department of Animal Resources, College of Agriculture, University of Baghdad, Iraq, was conducted to investigate the possibility of prediction of the total egg production from partial or cumulative egg production during one year after onset laying. Results revealed that weight at sexual maturity had no significant effect on all studied traits. Simple and multiple regressions were used to estimate prediction equations for the whole egg production from partial and cumulative egg production. It is concluded that the choice of the favorable prediction equations in dealing with partial egg production were that depended on second and third month egg production, whereas first 3 or 4 months could be the best choices in case of cumulative egg production.